2019
DOI: 10.1104/pp.18.01261
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Unfolded Protein Response Is Required for Normal Vegetative Development

Abstract: The unfolded protein response (UPR) is activated in plants in response to endoplasmic reticulum stress and plays an important role in mitigating stress damage. Multiple factors act in the UPR, including the membrane-associated transcription factor, BASIC LEUCINE ZIPPER 17 (bZIP17), and the membrane-associated RNA splicing factor, INOSITOL REQUIRING ENZYME1 (IRE1). We have analyzed an Arabidopsis (Arabidopsis thaliana) ire1a ire1b bzip17 triple mutant, with defects in stress signaling, and found that the mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 38 publications
(51 reference statements)
3
46
0
Order By: Relevance
“…Upon TM treatment, the atire1a atire1b double mutant showed over‐sensitivity phenotype compared with atire1a or atire1b single mutants and WT (Deng et al ), showing that the AtIre1 pathway is essential for UPR in Arabidopsis under extreme conditions. In addition, Yan et al (2019) reported that knockout of bZip17 has profound effects on vegetative development in the atire1a atire1b atbzip17 triple mutant background under normal condition (Bao et al ), revealing the UPR not only participates in development of Arabidopsis at a low active level under normal condition but is also highly regulated upon ER stress. Thus, UPR pathways are essential for plant reproductive and vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…Upon TM treatment, the atire1a atire1b double mutant showed over‐sensitivity phenotype compared with atire1a or atire1b single mutants and WT (Deng et al ), showing that the AtIre1 pathway is essential for UPR in Arabidopsis under extreme conditions. In addition, Yan et al (2019) reported that knockout of bZip17 has profound effects on vegetative development in the atire1a atire1b atbzip17 triple mutant background under normal condition (Bao et al ), revealing the UPR not only participates in development of Arabidopsis at a low active level under normal condition but is also highly regulated upon ER stress. Thus, UPR pathways are essential for plant reproductive and vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals and plants have shown that IRE1 executes essential functions in physiological growth (Bao, Bassham, & Howell, ; Chen & Brandizzi, ; Coelho & Domingos, ; Deng et al, ). The knockout alleles of the mammalian Ire1α , the Arabidopsis IRE1B, and the rice OsIRE1 are lethal in standard conditions of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the ire1b mutant has root elongation defects in recovery from temporary ER stress, suggesting that IRE1B is prominent in root growth in conditions of temporary ER stress recovery. Studies in animals and plants have shown that IRE1 executes essential functions in physiological growth (Bao, Bassham, & Howell, 2019;Chen & Brandizzi, 2013;Coelho & Domingos, 2014;Deng et al, 2016). The knockout alleles of the mammalian Ire1α, the Arabidopsis IRE1B, and the rice OsIRE1 are lethal in standard conditions of growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that TabZIP74 knockdown seedlings developed fewer lateral roots, while other studies have found that IRE1a and IRE1b support root growth in ways other than the splicing of bZIP60 mRNA (Deng et al, 2016). The growth of single or double bZIP60 mutants in combination with either bZIP17 or bZIP28 appear to be normal in unstressed conditions (Kim et al, 2018;Bao et al, 2019). Biotic stress, ER stress-inducing agent, ABA treatment, and drought could induce TabZIP74 mRNA splicing.…”
Section: Tabzip74 Involved In Wheat Drought Tolerance and Developmentmentioning
confidence: 92%
“…The ER stress triggers cytoprotective signaling pathways, titled the unfold protein response (UPR), this signaling pathway restores and maintains ER homeostasis. There is growing recognition that ER stress responses are involved in normal plant development (Deng et al, 2016;Kim et al, 2018;Bao et al, 2019); for example, ER stress is involved in the cells synthesizing and secreting materials comprising the pollen coat (Deng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%